Supply chain coordination in Confirming Warehouse Financing. (April 2018) - Lin, Qiang; Su, Xuemei; Peng, Ying
Highlights: A new SCF mechanism to coordinate the supply chain which aid a manufacturer that requires cash is proposed. Bank's interest rate is considered as an internal variable. We take the retailer's sales effort into consideration. Abstract: Numerous theories have been proposed to explore trade-credit in the presence of capital-constrained retailers. However, when manufacturers are also strapped for cash and can't afford the cost for long payback periods, trade-credit ceases to be operative. Confirming Warehouse Financing (CWF) is an innovative method of channel finance. It has shown great benefit in freeing up cash flow for both vendors and their retailers. While this new model was developed and tested empirically, it must also be examined through a theoretical perspective. For example, when demand is uncertain and affected by retailers' sales efforts, CWF, which typically requires complete buyback by the vendor, fails to properly coordinate the supply chain. This paper attempts to develop models to find the optimal mode under CWF to coordinate the supply chain. We examine three modified modes of CWF: (cash-advance discount compensation CWF, deposit withholding CWF and two-way compensation CWF). Our analytical results show that all three modes can achieve Pareto-Improvement, but only two-way compensation CWF can achieve proper supply chain coordination.